Penguatan UMKM Lokal Melalui Inovasi dan Digitalisasi: Studi Kasus Keripik Pisang di Desa Tratak - Astiko, Wahyu; Yarti, Suci; Idyawati, Idyawati; Azhari, Baiq Septia Vina; Wati, Karisma; Tanadi, Stephannie Nandhika; Nu’aimah, Siti Orpala; Juhanda, Rizki Aprilla; Haqqi, Ahmad Dia’ul; Ramadhan, Imam Muzhaffar; Ramdhani, Abi Irfan (Universitas Mataram, 2025)
Teratak Village in Batukliang Utara District, Central Lombok Regency, holds significant potential for agricultural product processing, particularly bananas. This community service program aims to empower local residents through flavor innovation, improved packaging, and digital marketing to enhance the competitiveness of banana chips as a flagship product. The activities involved training in producing multi-flavored banana chips such as chocolate, doger, and taro, developing attractive and eco-friendly packaging, and utilizing digital marketing strategies through platforms like Instagram and Facebook. The outcomes show that the community successfully created innovative flavors, designed informative labels, and adopted online marketing strategies to expand their market reach, including access to supermarkets and souvenir shops. This program has improved the community's skills and creativity, opened up new employment opportunities, and strengthened the identity of Teratak Village as a center of quality banana chip production. The integrated approach is expected to support sustainable local economic development.